A Recent Report on Occurrence of Mites on Commercial Mushrooms in Western Himalayas - , Asma Sherwani, Malik Mukhtar, Tahmina Mushtaq, Saima Maqsood, Parveena Bano, Mehreen Anees (Archives of Current Research International, 2024)
A large number of mites infest mushroom fruiting body and compost. These mites cause enormous damage to the fruiting body. An effort was made to identify different acarid mites and was undertaken at Department of Entomology and Mushroom Research and Training Centre, Faculty of Horticulture, Sher-e-Kashmir University of Agricultural Sciences and Technology, Shalimar under temperate conditions of Kashmir. During the present study four acarid mites were found in the mushroom culture. The mites were collected, reared in the laboratory on fruiting bodies of mushroom till the emergence of adult. The specimens were preserved in Oudemans fluid and send for identification. The samples were identified as Tyrophagus putrescentiae, Acarus siro, Pygmephorus sellnicki and Rhizoglyphus robini. These mites usually develop on rotting plant remains permeated by fungal hyphae and cause significant damage to mushroom fruiting bodies. This was the first report of mite infestation on commercial mushrooms in Kashmir.